Redescription of Ventania avellanedae (Stylommatophora: Odontostomidae), a land snail endemic to the Ventania Mountain System, Argentina - Piza, Julia (2018)
Although the presence of apertural folds and lamellae is the most recognizable character of the Odontostomidae, some species lack them, mostly in Anctus Martens, 1860, Bahiensis Jousseaume, 1877 and Moricandia Pilsbry & Vanatta, 1898. Eudioptus avellanedae Doering, 1881 - a slender odontostomid species that lacks even the slightest trace of folds or lamellae in its shell aperture - was however transferred to Odontostomus by Pilsbry in 1902 on the basis of its building forward of the aperture-margins. It is currently placed in its own monotypic subgenus, Cyclodontina (Ventania) Parodiz, 1940, on the basis of about the same argument. In this paper we redescribe its shell morphology and, for the first time, describe the internal anatomy of the pallial complex and the reproductive and digestive systems. The presence of a spongy gland in the pallial complex; of a short penis sheath with no retractor muscle; of a bursa copulatrix duct longer than spermoviduct, and of an epiphallic gland strongly support the inclusion of this unusual species in Odontostomidae. The species is diagnosable by the sculpture of the protoconch, which is not smooth as previously described, but has waved axial ribs crossed by spiral lines in young specimens; the distinctive external and internal shape of the bursa copulatrix duct; the internal penis wall divided in three regions of different sculpture; the smooth inner wall of the vagina; the long and cylindrical epiphallus with a distal widening indicating the presence of an epiphallic gland, and the penis retractor muscle inserted in the distal end of a short flagellum. These characters support the validity of Ventania Parodiz, 1940, different from Cyclodontina Beck, 1837.